Fidelização de um ídolo: Roberto Carlos - Samara, Beatriz Santos (2010)
This thesis aims at studying the reception developed during Roberto Carlos s artistic career. In order to achieve our goal, a biographical research and a field research both qualitative and quantitative were elaborated, so that the object is centered in the analysis of the process that constitutes a popular idol, its dialogue with the context of various decades, as well as the kind of communicative strategy that assured this artist permanent success and significant choice of preference. Initially, we have favored a synthetic directioning of his career in order to place the artist in the exercise of his art in contemporaneity. But because of his celebrity condition Roberto Carlos is a public personality somehow the dimension and significance of his success is well known. It is not by chance he is widely known as the King . The theoretical framework concurs on two inevitable matrices which, at the same time, justify this state of affairs and elucidate the strategic process of construction of success. As a consequence of this empiric basis, associated with the biographical research and with the analysis of the communicative process that built the idol RC, we hope we will contribute to contemporary studies on reception in development currently, especially those that concentrate on significances of wide recognition and popular response in the intricate process of communication